2022
DOI: 10.3390/nu14194005
|View full text |Cite
|
Sign up to set email alerts
|

Can Nutrition Play a Role in Ameliorating Digital Eye Strain?

Abstract: Digital eye strain is a complex, multifactorial condition that can be caused by excessive screen time exposure to various electronic devices such as smartphones, tablets, e-readers, and computers. Current literature suggests oxidative damage concomitant with a chronic pro-inflammatory state represent significant etiopathogenic mechanisms. The present review aims to discuss the potential dietary role for micronutrients with nutraceutical properties to ameliorate various ocular and vision-related symptoms associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 318 publications
0
5
0
Order By: Relevance
“…In the treatment of androgendeficient dry eye in rats, it has been found to improve the amount of the aqueous part and maintain tear film stability, as well as inhibit inflammation of the lacrimal gland [65]. The role of diet (omega-3 fatty acids, flavonoids, carotenoids) on the state of the organ of vision is studied especially in users of VDT screen monitors [66]. Supplementation with bilberry extract improved some objective and subjective parameters of eye fatigue induced by screen monitor loads [67,68].…”
Section: Discussionmentioning
confidence: 99%
“…In the treatment of androgendeficient dry eye in rats, it has been found to improve the amount of the aqueous part and maintain tear film stability, as well as inhibit inflammation of the lacrimal gland [65]. The role of diet (omega-3 fatty acids, flavonoids, carotenoids) on the state of the organ of vision is studied especially in users of VDT screen monitors [66]. Supplementation with bilberry extract improved some objective and subjective parameters of eye fatigue induced by screen monitor loads [67,68].…”
Section: Discussionmentioning
confidence: 99%
“…Treatment modalities using specialized filter glasses and optimizing the screens of digital devices have been explored with equivocal results. 42 Meanwhile, adjunctive nutraceutical strategies involving xanthophyll macular carotenoids have shown promising results in ameliorating DES-related visual symptoms and enhancing cognitive functions. 43 …”
Section: Digital Eye Strain/ Computer Vision Syndromementioning
confidence: 99%
“…All of these have affected our productivity and have put a great impact an individual's quality of life. 4 A study conducted at the University of Khartoum, Sudan have reported 94% prevalence of CVS. 5 Lema et al in their systematic review concluded that almost two in three individuals have CVS with high prevalence among women.…”
Section: Understanding Computer Vision Syndromementioning
confidence: 99%
“…7,8 Additionally, studies suggest that CVS can worsen existing vision problems such as nearsightedness or astigmatism. 3,4…”
Section: Understanding Computer Vision Syndromementioning
confidence: 99%